2014
DOI: 10.1016/j.jacr.2014.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Improving Diversity, Inclusion, and Representation in Radiology and Radiation Oncology Part 1: Why These Matter

Abstract: The ACR Commission for Women and General Diversity is committed to identifying barriers to a diverse physician workforce in radiology and radiation oncology (RRO), and to offering policy recommendations to overcome these barriers. In Part 1 of a 2-part position article from the commission, diversity as a concept and its dimensions of personality, character, ethnicity, biology, biography, and organization are introduced. Terms commonly used to describe diverse individuals and groups are reviewed. The history of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
89
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 166 publications
(94 citation statements)
references
References 34 publications
1
89
0
1
Order By: Relevance
“…The benefits of diversity within higher education and the field of medicine have been widely studied. [1][2][3][4][5][6] Gurin et al 2 demonstrated a positive relationship between interaction with a diverse set of peers and educational outcomes in undergraduate education. Educational benefits of diversity have been documented in medical school for both white and underrepresented minority students: a survey of white medical students who attended programs with the highest quintile for racial and ethnic diversity were "more likely to rate themselves as highly prepared to care for minority populations compared with those from schools in the lowest quintile for diversity."…”
Section: Introductionmentioning
confidence: 99%
“…The benefits of diversity within higher education and the field of medicine have been widely studied. [1][2][3][4][5][6] Gurin et al 2 demonstrated a positive relationship between interaction with a diverse set of peers and educational outcomes in undergraduate education. Educational benefits of diversity have been documented in medical school for both white and underrepresented minority students: a survey of white medical students who attended programs with the highest quintile for racial and ethnic diversity were "more likely to rate themselves as highly prepared to care for minority populations compared with those from schools in the lowest quintile for diversity."…”
Section: Introductionmentioning
confidence: 99%
“…Diversity serves as a catalyst for creativity and generates opportunities to embrace new perspectives. 8,9 To harness such wealth, inequities, including those based on gender, must be swiftly addressed. 6 Authorship patterns may also be affected by implicit bias among reviewers.…”
Section: Introductionmentioning
confidence: 99%
“…Radiology leaders committed to increasing gender diversity and fostering an inclusive workplace have the opportunity to strengthen their organizations. Developing a radiology culture supportive of the needs of women and conducive to physician well-being will broaden radiology's horizons by improving workplace innovation, growth, and collaboration (2).…”
Section: Introductionmentioning
confidence: 99%